Antiviral Activity and Safety of Darunavir/Cobicistat for the Treatment of COVID-19. (21st June 2020) - Chen, Jun; Xia, Lu; Liu, Li; Xu, Qingnian; Ling, Yun; Huang, Dan; Huang, Wei; Song, Shuli; Xu, Shuibao; Shen, Yingzhong; Lu, Hongzhou
Abstract: Background: We aimed to evaluate the antiviral activity and safety of darunavir/cobicistat (DRV/c) in treating COVID-19 patients. Methods: In this single-center, randomized, and open-label trial, mild patients with polymerase chain reaction (PCR)–confirmed COVID-19 were enrolled in Shanghai, China. Participants were randomized to receive DRV/c for 5 days on the top of interferon alpha 2b inhaling or interferon alpha 2b inhaling alone. The primary end point was the virological clearance rate of oropharyngeal swabs at day 7 after randomization in the intention-to-treat population (clinicaltrials.gov: NCT04252274). Results: From January 30, 2020, to February 6, 2020, a total of 30 patients were enrolled, of whom 18 (60%) were male, aged 47.2 ± 2.8 years; 63.3% (19/30) of the participants had fever, and 46.7% (14/30) had cough at enrollment. The participants were randomized (range) at 4 (2–5) days after onset of symptoms. The proportion of negative PCR results at day 7 was 46.7% (7/15) and 60.0% (9/15) in the DRV/c and control groups ( P  = .72), respectively. The viral clearance rate at day 3 was 20% (3/15) in both study groups, while the number increased to 26.7% (4/15) in the DRV/c group and remained 20% (3/15) in the control group at day 5. Fourteen days after randomization, 1 participant in the DRV/c group progressed to critical illness and discontinued DRV/c, while all the patients in the control group were stable ( P  = 1.0). The frequencies of adverse events in the 2 groups were comparable. Conclusions: Five days of DRV/c did not increase the proportion of negative conversion vs standard of care alone, although it was well tolerated.